Memory reconsolidation of an inhibitory avoidance task in mice involves cytosolic ERK2 bidirectional modulation - Krawczyk, Maria del Carmen (2015)
Reconsolidation has been defined as the process of memory stabilization after retrieval involving, among others, gene expression regulation and post-translational modifications. Many of these mechanisms are shared with memory consolidation. Here, we studied hippocampal ERK participation on memory reconsolidation of an inhibitory avoidance task in CF-1 mice. We found a retrieval-induced cytosolic ERK2 activation in the hippocampus (HIP) 15. min after memory reactivation, and an inhibition at 45. min. PD098059, a MEK1/2 (MAPK/ERK kinase) inhibitor, administered in the HIP immediately after retrieval impaired memory in a dose-dependent fashion. However, infusions of the highest dose of PD098059 performed 40. min after retrieval enhanced memory in mice trained with a weaker footshock. These results suggest for the first time that ERK2 is involved in memory reconsolidation in a biphasic fashion. Furthermore, the inhibition of ERK could either impair or enhance mice performance depending on ERK state of activation.